The right to education for people deprived of their liberty: a research-action (Research, Society and Development, 2022)
The research conducted had the objective of promoting the textual production of prisoners in the Province of Lunda Norte, Angola, in order to identify its constitutive elements, the predominant narratives and the use of writing skills both in the affirmation of identity and in the affirmation of rights. Understanding that education is done throughout life, at all times, in all spaces, and that the writing of prisoners constitutes a Prison Literature yet to be thematized by academic research, we developed the study by offering literary workshops for later analysis of the materials produced. Thinking about the right to education in prison means reflecting on its contribution to the lives of prisoners and society in general; the offer of educational activities in spaces of deprivation of freedom has specificities that differentiate it from other spaces. It is an opportunity for socialization, in the sense that it offers the participants new references, the possibility of identity reconstruction, and the rescue of lost citizenship. Through the development of the research, we confirmed the hypothesis that, in a prison population with access only to Bible reading and little stimulus to reading and writing, the context of incarceration, by itself, is capable of producing an epistemology that translates into narratives of interest to the field of Education.